The Descriptive Analysis of Students’ Ability in Writing Descriptive Text at the Eight Grade of SMP Negeri 3 Sirombu in 2021/2022 - Kristof Martin Efori Telaumbanua (Journal on Education, 2024)
Writing is a process of extracting and conveying the meanings in one's head into words on a piece of paper. The Syllabus of SMP Negeri 3 Sirombu expects students to be able to write several texts and one of them is descriptive text. The aim of the research is to describe students' abilities and the factors that influence them. The method used in this research is descriptive qualitative. Data analysis was carried out by following Gay et al's steps, namely reading/memoing, describing what happened in the setting, and classifying research data. Furthermore, the informants for this research were 18 class VII students at SMP Negeri 3 Sirombu. Data was collected through student worksheets and interviews with students and English teachers. After analyzing students' descriptive texts, the results showed that 7 students (38.8%) were able to write descriptive texts, and only 11 students (61.1%) were unable to write descriptive texts. After analyzing the students' answers on the interview sheets, the results showed that many different factors influenced their writing. In conclusion, most of the VIII students of SMP Negeri 3 Sirombu were able to write descriptive texts with aspects of good writing based on several main factors, namely their background knowledge about the topic, their level of understanding of descriptive texts, their learning.